Lieu partagé, jeu magnifié : protocole spectaculaire à la pré-Renaissance anglaise - André Lascombes (Anglophonia)
This essay argues that certain key factors lie behind the successful rapport that existed between late XVth and early XVIth interludes and their socially mixed audiences. The first is the capacity of the play area to elicit in the audience a sense of simultaneous participation in the world of the play, and that of their social environment. Besides the various techniques of linguistic exchange, factors such as acting style and the frequent use of doubling and masking further served to reinforce a type of audience reception based on what one may term «diaphoric vision». Such authentic illusio is much richer and more pleasurable than «reality-based illusion» achieved through the realistic codes increasingly in use today.